2018
DOI: 10.3390/molecules23071810
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidation and Melanogenesis Inhibition of Various Dendrobium tosaense Extracts

Abstract: This study investigated the polyphenol content, antioxidant activity, and inhibition ability of mushroom tyrosinase and melanogenesis of Dendrobium tosaense (DT) extract. Ground DT was extracted using deionized water (W) or 50% ethanol (50E) at room temperature (RT) or 50 °C (50T) for 20 min. The 50T + 50E extract exhibited the highest total phenol content 47.0 ± 4.0 mg gallic acid equivalent/g DT extract, the highest level of 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) free-radical scavenging 66.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 26 publications
(34 reference statements)
1
28
0
Order By: Relevance
“…The total phenolic content of the tea sample was determined using the Folin-Denis method devised in previous reports [16][17][18]. Every black tea sample was mixed with 0.8 mL of Folin-Denis reagent for 3 min.…”
Section: Determination Of Total Phenolic Contentmentioning
confidence: 99%
“…The total phenolic content of the tea sample was determined using the Folin-Denis method devised in previous reports [16][17][18]. Every black tea sample was mixed with 0.8 mL of Folin-Denis reagent for 3 min.…”
Section: Determination Of Total Phenolic Contentmentioning
confidence: 99%
“…As mentioned in the previous reports [14][15][16], the present study uniformly mixed 50 μL of 198 μM DPPH ethanol solution and 50 μL of the SCG extract solution; the mixture was allowed to react in darkness for 30 minutes. Optical absorbance at 517 nm was measured using a spectrophotometer; a low optical absorbance reading indicated that the sample had high DPPH free-radical scavenging activity.…”
Section: Dpph Free-radical Scavenging Activity Assaymentioning
confidence: 99%
“…Following previous methods [14][15][16], the present study uniformly mixed 250 μL of 7 mM ABTS with 250 μL of 2.45 mM potassium peroxydisulfate; the mixture was allowed to react at 4°C in darkness for 16 hours.…”
Section: Abts Free-radical Scavenging Activity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few decades, research has demonstrated that natural bioactive compounds are increasingly being used in whitening cosmetic formulations. In addition, there are several plant extracts that have been shown to be effective agents to suppress the overproduction of melanin or to regulate melanin synthesis, such as Cassia fistula flowers [31], Asphodelus microcarpus [32], Magnolia officinalis [33], Dendrobium tosaense [34], and Kummerowia striata [35]. The results of the present study indicated that extracts of E. elatior flowers and leaves achieved a decent skin whitening effect on human volunteers; therefore, these extracts act as the active whitening ingredient in FL1 cream.…”
mentioning
confidence: 99%